‘And we may not even touch a hair of our kitchen maid’s head’. Advantages and disadvantages for owners of monuments and historic buildings (Bulletin KNOB, 2012)
When Dutch legislation on monuments and historic buildings was developed, the discussion was mainly determined by the question whether the importance of preservation of monuments and historic buildings was in proportion to the infringement of an individual owner’s exercise of his property rights such protection would imply. This discussion is still relevant. The legislator’s choice to focus on the owner in the recent modernisation of preservation of monuments and historic buildings is also part of it. This article describes the history of the development of the Monuments and Historic Buildings Act 1961 against the light of this continuing debate on the proportionality of the infringement. The (Royal) Netherlands Archaeological Association (NOB) played a prominent part in this history.Since its foundation in 1899 the NOB, following the surrounding countries, argued the necessity of realizing legal protection of monuments and historic buildings. The first step towards – or of – institutionalized preservation of monuments and historic buildings was made in 1903 by means of a broadly arranged inventory of monumental buildings and objects. In 1907 the Association set up an expert committee to advise on a legal framework for the preservation of monuments and historic buildings. This legal instrument had to supplement the existing practice of subsidizing restoration. In 1910 the final report of the committee appeared with recommendations to the legislator. Among other things, they gave the advice to include owners’ liability for maintenance.In spite of various announcements of a Monuments and Historic Buildings Act, successive cabinets kept shrinking from infringing on property rights, which they regarded as a practically absolute right. Consequently, imposing limitations was problematic and imposing obligations for owners of historic buildings (too) drastic. The aim to bring policy in line with religious communities and objections of interest groups from the notarial profession and mortgage lenders did not speed up the process either.The war damage during the Second World War led to temporary measures for the protection of monuments and historic buildings. After the war these measures were extended several times and in the fifties a real Monuments and Historic Buildings Act was prepared. Initially, a liability for maintenance was still included, so as to be able to force reluctant owners to execute maintenance work, in the worst-case scenario. At the last moment the Articles in question were deleted after all, because the legislator considered this liability too large an infringement of property rights and hence irresponsible. Maintenance would only be stimulated by a subsidy programme. The KNOB stated that this implied that the Act had lost its force from the very start. Nevertheless, the chosen system of the Monuments and Historic Buildings Act 1961 was indeed in line with the advice of the Association in 1910. Fifty years’ experience with the Monuments and Historic Buildings Act did not put an end to the criticism of the supposed infringement of property rights and the subject still receives plenty of attention from the legislator.